If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 2c + 3 = 7 + c Reorder the terms: 6 + 3 + 2c = 7 + c Combine like terms: 6 + 3 = 9 9 + 2c = 7 + c Solving 9 + 2c = 7 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. 9 + 2c + -1c = 7 + c + -1c Combine like terms: 2c + -1c = 1c 9 + 1c = 7 + c + -1c Combine like terms: c + -1c = 0 9 + 1c = 7 + 0 9 + 1c = 7 Add '-9' to each side of the equation. 9 + -9 + 1c = 7 + -9 Combine like terms: 9 + -9 = 0 0 + 1c = 7 + -9 1c = 7 + -9 Combine like terms: 7 + -9 = -2 1c = -2 Divide each side by '1'. c = -2 Simplifying c = -2
| 13k^2+26k+13= | | X(x-2a)+a^2+1=0 | | w^6+8w^3+7=0 | | d^6+2d^3-80=0 | | 9a+26c+2ab+13c+4ab-9b= | | -14y=7x+1 | | 12a^3b^2-27ab^2=0 | | 4(1-x)+7x=4 | | 18x^3-27x^2-2x+3=0 | | a^3b^3+64=0 | | 5x+3(2x-9)=17 | | 30y^3+12y^2+5y+1=0 | | =126 | | 5(3a+5b)= | | 24c^2-24c+6=0 | | (3x-1)(2x+4)-(3x-1)(x+1)=(3x-1)(2x-3) | | 1.5x+4=1 | | 10n=9n+5 | | -3(m-2)+6m=9(m-1) | | -8b+b+13ab= | | 2kx-2ky-12=0 | | x^3-15x^2-5x-52=0 | | 5x-1=3(2x+4) | | 2ad-9b+-8b= | | 5x=19+y | | -[8z-(11z+4)]=4+(2z+0) | | 4x^2-x+4=04 | | 2(x+3)+3x=51 | | 13c+4ab-9b= | | 15x^3-15x^2-5x-52=0 | | (x-0)(x-3)(x-5)=0 | | x*8=28 |